Association Between Pulmonary Hypertension and Transcatheter Aortic Valve Replacement: Analysis of a Nationwide Inpatient Sample Database - Zoltowska, Dominika M.; Agrawal, Yashwant; Patel, Nilesh; Sareen, Nishtha; Kalavakunta, Jagadeesh K.; Gupta, Vishal; Halabi, Abdul (Reviews on Recent Clinical Trials, 2019)
Introduction: This study was done to review the association of pulmonary hypertension (PH) with Transcatheter Aortic Valve Replacement (TAVR) procedures done in the US for years 2010 to 2012. Methods: We used Nationwide Inpatient Sample (NIS) data to extract data for patients who were hospitalized with a primary/secondary diagnosis of TAVR as specified by International Classification of Disease (ICD-9) codes 35.05 and 35.06. PH was identified with ICD-9 codes 416.0 and 416.8. Logistic regression models were used to analyze the association between PH and clinical outcomes of TAVR. Results: A total of 8,824 weighted discharges were identified with a primary/secondary diagnosis of TAVR, of which 1,976 (22.4%) also had PH. Mean age of patients undergoing TAVR with and without PH was 81.4 and 81.1 years, respectively. More females had a diagnosis of PH with TAVR when compared to males, (56.9% vs. 43.1). When controlling for demographics, diabetes and hypertension; the association between PH and TAVR was statistically significant (p<.0001). Estimated odds of TAVR with PH was 5.46 (95% CI: 4.63, 6.41) times greater than for TAVR without PH. Similarly, the estimated odds for a length of stay greater than 1 week for TAVR with PH was 1.43 (95% CI: 1.12, 1.82; p=.0034) times greater than odds for TAVR without PH. PH was not statistically significant for in-hospital mortality in patients receiving TAVR (p=0.7067). Conclusion: This study suggests that underlying PH does not influence the immediate mortality of patients underlying TAVR. Further studies are needed to delve into the bearing of PH on TAVR.
Keywords: pulmonary hypertension